Variant analysis from bacterial isolates affirms DnaK crucial for multidrug resistance - Mujawar, Shama *; Amr, Adel A.; Lahiri, Chandrajit * (Springer, 2020)
Next-generation sequencing and associated computational analyses have become powerful tools for comparing the whole genomes and detecting the single nucleotide polymorphisms (SNPs) within the genes. In our study, we have identified specific mutations within the plausible drug resistant genes of eight multidrug resistant (MDR) bacterial species. Essentially, we have unearthed few proteins, involved in folding and enabling survival under stress, to be the most crucial ones from the network of the whole genome protein interactome (PIN) of these species. To confirm the relevance of these proteins to antibiotic resistance, variant analyses were performed on all the selected MDR species, isolated from patients’ samples in PATRIC database, against their respective reference genomes. The SNPs found in the patient isolates revealed the nucleotide changes from C to A on DnaK, thereby altering a single amino acid change that might lead to misfolding of proteins. Thus, we propose DnaK to be the best characterized bacterial chaperone having implications in multidrug resistance. To this end, to provide an alternative solution to tackle MDR, docking studies were performed with a phenaleno-furanone derivative which revealed the highest binding energy and inhibition against DnaK.